BREEDING, AGE AND GROWTH OF THE FRESHWATER SHARK WALLAGO ATTU (BLOCH AND SCHNEIDER) FROM THE DHIR BEEL OF THE BRAHMAPUTRA BASIN, ASSAM, INDIA. - GOSWAMI, P. K.; DEVARAJ, M. (Journal of Indian Fisheries Association, 2015)
The Dhir becl, one of the major live becls of the Brahmaputra basin, Assam, has anarea of 689 ha and is situated in Dhubli district of Assam. The dominance of freshÂ·watershari